Bosco

avatar
Имя пользователяBosco
Гол1338
Membership
Stats
Вопросов 0
ответы 761

 #1
avatar+1338 
0

 

Let a1, a2, a3, ..., a10 be an arithmetic series. If a1 + a3 = -2 and a2 + a4 + a6 = 1, then find a1.    

 

Call "d" the amount of addition between successive terms.    

 

Starting with a1   then  a1  =  a1                                                    =   a1    

                                    a2  =  a1 + d                                              =   a1 + d     

                                    a3  =  a2 + d  =  (a1 + d) + d                     =   a1 + 2d    

                                    a4  =  a3 + d  =  (a1 + d + d) + d               =   a1 + 3d    

                                    a5  =  a4 + d  =  (a1 + d + d + d) + d         =   a1 + 4d    

                                    a6  =  a5 + d  =  (a1 + d + d + d + d) + d   =   a1 + 5d    

 

given       a1 + a3  =  – 2    

                a1 + (a1 + 2d)  =  – 2    

                2a1 + 2d  =  – 2    

                     a1 + d  =  – 1                                   (eq 1)    

 

given        a2 + a4 + a6  =  1    

                (a1 + d) + (a1 + 3d) + (a1 + 5d)  =  1    

                3a1 + 9d  =  1                                       (eq 2)    

 

multiply (eq 1) by – 9         – 9a1 – 9d  =  9    

add (eq 2)                             3a1 + 9d  =  1    

                                           – 6a1          =  10    

                                                a1          =  – 10 / 6    

                                                        a1  =  – 5 / 3    

.    

29 янв. 2025 г.
 #1
avatar+1338 
0

 

Let a_1, a_2, a_3, \dots, a_8, a_9, a_{10} be an arithmetic sequence. If $a_1 + a_3 = 5$ and $a_2 + a_4 = 6$, then find $a_1$.    

 

call "d" the amount of addition between successive terms.    

 

starting with a1   then  a2  =  a1 + d                                              =   a1 + d     

                                    a3  =  a2 + d  =  (a1 + d) + d                     =   a1 + 2d    

                                    a4  =  a3 + d  =  (a1 + d + d) + d               =   a1 + 3d    

                                    a5  =  a4 + d  =  (a1 + d + d + d) + d         =   a1 + 4d    

                                    a6  =  a5 + d  =  (a1 + d + d + d + d) + d   =   a1 + 5d    etc. . . .    

 

given       a1 + a3  =  5   

                a1 + (a1 + 2d)  =  5   

                2a1 + 2d  =  5                                   (eq 1)    

 

given        a2 + a4  =  6   

                (a1 + d) + (a1 + 3d)  =  6   

                2a1 + 4d  =  6    

                  a1 + 2d  =  3                                    (eq 2)    

 

Subtract (eq 2) from (eq 1)    

                                               2a1 + 2d  =  5      (eq 1)    

                                                 a1 + 2d  =  3      (eq 2)    

                                                 a1          =  2    

.    

27 янв. 2025 г.